AcRR1 of Agropyron cristatum boosts wheat yield by regulating grain number per spike and heading date - Wenjing Yang; Haiming Han; Huihui Ma; Ping Yang; Jianqing Niu; Xinye Liu; Jinpeng Zhang; Shenghui Zhou; Kai Qi; Baojin Guo; Yida Lin; Xinming Yang; et al. (Nature Communications)
Abstract Uncovering desirable alien genes from wild species is important for increasing genetic variation and ensuring wheat production. Here, we identify a type-B response regulator (RR) AcRR1 of Agropyron cristatum. Ectopic expression of AcRR1 in common wheat increases the grain number per spike without decreasing the grain weight, thereby enhancing the grain yield by 9.7‒12.3% under field conditions. Expression of the AcRR1 gene also promotes plant growth and shortens the duration of vernalization in the transgenic plants. We reveal that AcRR1 reprogrammes diverse transcriptional processes in wheat by activating the expression of TaWOX11-2D and TabHLH25-5B–TaFTs, which are involved in floret fertility and early heading. Our results demonstrate that AcRR1 from A. cristatum is a valuable alien gene with the capacity to activate genetic networks for wheat yield formation, offering a promising avenue for enhancing wheat productivity through the introduction of alien genes.